Arthroscopic Microfracture for Osteochondral Lesions of the Talus: Second-Look Arthroscopic and Magnetic Resonance Analysis of Cartilage Repair Tissue Outcomes. (2nd January 2020) - Yang, Hong-Yeol; Lee, Keun-Bae
Abstract : Background: Arthroscopic microfracture is considered the primary treatment strategy for osteochondral lesions of the talus and has been shown to provide successful outcomes. However, deterioration of clinical outcomes and fibrocartilage infill over time is now a recognized concern. The purpose of the present study was to evaluate the outcomes related to cartilage repair tissue after microfracture with use of second-look arthroscopy and magnetic resonance imaging (MRI) and to compare these findings with functional outcomes. Methods: Twenty-five patients underwent second-look arthroscopy and MRI at a mean of 3.6 years (range, 2.2 to 8.1 years) after microfracture. Second-look arthroscopic findings were assessed according to the system of the International Cartilage Repair Society (ICRS). MRI was evaluated postoperatively with use of the magnetic resonance observation of cartilage repair tissue (MOCART) score. Clinical outcomes were determined with use of the Foot and Ankle Outcome Score (FAOS), the American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot scale, and the Short Form-36 (SF-36) score. Results: On second-look arthroscopy, 9 ankles (36%) were still abnormal according to the ICRS overall repair grades. The average postoperative MOCART score was 67.8 (range, 30 to 95), with good association with functional outcome. In addition, 6 patients (24%) had a mismatch between the MRI and second-look arthroscopic findings. Significant improvements were observed in all functional outcome categories between the preoperative and latest follow-up evaluations (p < 0.001). The mean FAOS scores for ICRS repair grades I and II (n = 16) and grades III and IV (n = 9) were 86.8 and 75.6, respectively. There was a significant correlation between FAOS scores and ICRS grades (p = 0.004). Conclusions: Second-look arthroscopic results revealed that 36% of lesions were incompletely healed and had inferior quality of repair tissue compared with that of native cartilage at a mean of 3.6 years, although arthroscopic microfracture provided functional improvements. Magnetic resonance analysis demonstrated some limitations in comparison with arthroscopy for the evaluation of cartilage repair. Therefore, second-look arthroscopy has an important role in accurately assessing the status of the cartilage repair tissue beyond the use of the MOCART score and functional outcomes. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.